Analysis of the quality of the shredder plastic machine depend on variations in material plastic types and dimensions using the Taguchi Method - Hendra Hendra; Nur Qodri Wijayanto; Sidik Susilo; Erny Listijorini; Hernadewita Hernadewita (Jurnal Teknika, 2023)
The problem of plastic waste is critical things because everybody still often uses plastic for various daily needs. Therefore, recycling is considered very important to overcome these problems, including using a plastic chopping machine. The types of plastics used in this research are HDPE, PE, and PP plastics with experimental methods and the Taguchi method to determine the effect of plastic variations, the dimensions of the chopped results, and the percentage value of the contribution of the test variables to the plastic chopping machine. The results obtained in the study are that all types of plastics can be adequately chopped, with the optimum size for PP plastic being 6,8 x 4,5 mm with a processing time of 91,5 seconds. For PE, it is 16 x 10. 5 mm with a processing time of 170.6 seconds. While for HDPE, it is 68 x 34.5 mm with a processing time of 251.1 seconds. These results follow those obtained using the Taguchi method, with a contribution percentage of 77 % for the variable type of plastic followed by dimensions, weight, and thickness.